The preliminary analysis of protein catabolism and nitrogen balance in young gymnasts - Sawicki, P.; Kaczor, J.J. (Science & Sports, 2018)
Objectives: The use of proper diet in athletes is one of the most important elements of sports training. Moreover, the essentials in planning diet for athletes among other things should be taken into account: energy balance, the nutritional value of meals and supplements of diet. The main aim of this study was to estimate the level of whole body proteins catabolism, nitrogen and energy balance in young gymnasts. Methods: In the present study participated young gymnastics (13.0±0.5year), which have been trained artistic gymnastics since 6.8±0.45year. The investigation contained two times measuring urea in 24h urine collection, measuring energy expenditure indirect method by 24h monitoring heart rate, and supplementation by 7days products contain protein and carbohydrate. Results: Concentration of urea nitrogen in urine at the first test before supplementation was 8.0±0.75g/d. The energy expenditure in young boys before supplementation was negative (-915±130kcal). The concentration of urea nitrogen was lower in 4 out of 5 examined boys as compared to the first test after supplementation. The difference between the level of nitrogen balance output and the level after supplementation was statistically significant (P=0.05). Conclusion: The supplementation with proteins and carbohydrates products immediately after training may lead to decrease concentration of urea nitrogen and whole body protein catabolism. Monitoring energy expenditure, food nutrients, and calories in diet during and after training should be an integral part of planning for long-term training program.